Social Sanction Ditinggian Janjang Against Violation of Traditional Law in Koto Gadang Preparation Nagari, Baso District, Agam Regency - Ulfia Hasanah; Latifah Alkhairiyah; Susilawati Susilawati; Sabrena Sukma (Unram Law Review, 2021)
Based on research data, it is found that many teenagers in Indonesia have had sex before marriage. This behavior is not by the norms that apply in Indonesia, and of course, this deviant behavior will cause new problems in society. In Nagari Preparation Koto Gadang, West Sumatra, a social sanction was imposed on community members who violated Adat. This sanction is known as the social sanction "Ditinggian Janjang." But, it is not yet known how applying this sanction in the community can reduce the number of violations committed by the community, one of which is promiscuity. This study aims to determine the application and role of social sanctions in Ditinggi Janjang. The author's research method is sociological-normative with bibliographic sources and observes the characteristics of a community's behavior in an area in an aspect of social life, observation, interviews, and documentation. Based on the study results, it can be seen that the application of social sanctions is applied to the entire community. The role of ditinggan janjang’s social sanctions is to prevent and solve various problems, especially those related to free sex in the community, in preparation for Nagari Persiapan Koto Gadang, Baso District, Agam Regency, West Sumatra Province. Keywords: Customary Law; Violators; Social Sanctions; Nagari Based on research data, it is found that many teenagers in Indonesia have had sex before marriage. This behavior is not by the norms that apply in Indonesia, and of course, this deviant behavior will cause new problems in society. In Nagari Preparation Koto Gadang, West Sumatra, a social sanction was imposed on community members who violated Adat. This sanction is known as the social sanction "Ditinggian Janjang." But, it is not yet known how applying this sanction in the community can reduce the number of violations committed by the community, one of which is promiscuity. This study aims to determine the application and role of social sanctions in Ditinggi Janjang. The author's research method is sociological-normative with bibliographic sources and observes the characteristics of a community's behavior in an area in an aspect of social life, observation, interviews, and documentation. Based on the study results, it can be seen that the application of social sanctions is applied to the entire community. The role of ditinggan janjang’s social sanctions is to prevent and solve various problems, especially those related to free sex in the community, in preparation for Nagari Persiapan Koto Gadang, Baso District, Agam Regency, West Sumatra Province.